Aktivitas Antirayap Ekstrak dan Fraksi Biji Jeruk Sambal (Citrus microcarpa Bunge) Terhadap Rayap Tanah (Coptotermes curvignathus Holmgren) - Jayatri, Rahmi; Warsidah, Warsidah; Rudiyansyah, Rudiyansyah (Jurnal Kartika Kimia, 2023)
Citrus microcarpa is one of the Rutaceae family plants which is commonly used for food industries to enhance aroma and flavor. This plant contains secondary metabolites such as terpenoids, flavonoids, and phenolics. Unfortunately, bioactivity information, specifically anti-termites from citrus seeds is unreported. The aim of this study was to determine anti termite activity of the methanol extract and fractions of the citrus seeds against Coptotermes curvignathus Holmgren. The research was carried out in several stages, starting from maceration, partitioning, phytochemical testing, and termite activity testing for 7 days. The results of the subterranean termite mortality test were justified based on the LC50 values, from the smallest to the largest values, respectively, chloroform fraction 1.689%, methanol fraction 1.783%, n-hexane fraction 1.788%, and methanol extract 2.324%. The results of termite mortality which reached 100% for each tested sample were due to the extract and fractions of the citrus seeds have antifeedant activities.